Fouling of ultrafiltration membrane during adsorption of long chain fatty acid in glycerine solutions - Abdul Wahab Mohammad,; Indok Nurul Hasyimah Mohd Amin, (Universiti Kebangsaan Malaysia, 2013)
Membrane fouling caused by the adsorption of fatty acids limits the application of membrane technology in oleochemical industry especially for the pretreatment of glycerin-rich solution. The aim of the work presented in this paper was to understand the adsorptive fouling of palm oil based fatty acid on ultrafiltration membranes. The influence of solution pH, molecular weight cut-off (MWCO) and hydrophobicity of the membrane were studied. Oleic acid was used as a foulant, representing the long chain palm oil based fatty acid in glycerol−water solution. The outer membrane exposed to the mixtures for 6 h without pressure. The stirring speed was set at 300 rpm and polyethersulfone (PES) membranes with MWCO of 5, 20 and 25 kDa were used. The adsorptive fouling was determined using the relative flux reduction (RFR) method. It is demonstrated in this study that PES membranes are susceptible to the deposition of fatty acids on the membrane surface and pores. The fouling phenomenon at low pH is more severe than that of high pH due to the attractive force between solutes and the membrane. The PES membranes after adsorption were characterized by contact angle and Fourier transform infrared (FTIR), while the surface was visualized with scanning electron microscopy (SEM).